Book Reviews (The Muslim world, 1962)
Book reviewed in this article: The Nestorians and Their Neighbors. Study of Western Influences on Their Relations. By John Joseph. The Theology of the Christian Mission. Edited and with an introduction by Gerald H. Anderson. Al-Azhar: A Millennium of Muslim Learning. By Bayard Dodge. The Agricultural Policy of Muhammad cAli in Egypt. By Helen Anne B. Rivlin. The Industrialization of Iraq. By Kathleen M. Langley. Manpower and Oil in Arab Countries. By Albert Y. Badre and Simon G. Siksek. Contemporary Arab Politics. By George E. Kirk. Frederick A. Praeger. Faces in Shem. By D. van der Meulen. Lebanon in the Last Years of Feudalism: 1840-1868. By Antun Dahir al-cAqiqi; translation and commentary by Malcolm H. Kerr. Akhbār al-Buhturi. By Abū Bakr Muhammad. The Middle East, 1961, eighth edition. The Religion of Java. By Clifford Geertz. The Land and People of Indonesia. By Datus C. Smith, Jr. J. B. Lippincott. Kitāb el-Radd alā‘I-Ǧahm?ya des Abū Sa?d ‘Uthmān b. Sa?d al-Dārim?. Nach der in der Köprülübibliothek aufbewahrten Handschrift (Cod. 850) zum ersten Male herausgegeben und mit Einleitung und Kommentar versehen von Gösta Vitestam. A Dictionary of Moča. (Southwestern Ethiopia). By Wolf Leslau.